Pengaruh Senam Hamil Terhadap Persalinan Pervaginam Pada Ibu Hamil Primigravida di Wilayah UPT Puskesmas Narumonda Kecamatan Siantar Narumonda Kabupaten Toba - Simarmata, Desi Rosmaulina; Manurung, Herna Rinayanti; Chandra Siagian; Nahampun, Sri Anju Prayuni; Elni Arizona Hutagaol, Elni Arizona; Hutajulu, Donna Agnes (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Pregnancy exercise is an exercise program for healthy pregnant women to prepare the mother’s physical condition by maintaining the condition of the muscles and joints that play a role in the delivery process, as well as preparing for the mother’s condition, especially growing confidence in facing childbirth. Purpose: This study aims to determine the relationship between pregnancy exercise and vaginal delivery in primigravida in the UPT area of the Narumonda Health Center, Siantar Narumonda District, Toba Regency. Method: carried out in an analytical survey, then analyzes the dynamics of the correlation between these phenomena. The time approach used is retrospective, namely research that starts from the effect or dependent variable. The sample is 34 primigravida, taken using purposive sampling technique. Result: Data analysis technique using chi square. There is a relationship between pregnancy exercise and the time of vaginal delivery in primigravida in the Upt Area of the Narumonda Health Center, Siantar Narumonda District, Toba Regency. There is an Influence of Pregnancy Exercise on Vaginal Delivery in primigravida in the Upt Area of the Narumonda Health Center, Siantar Narumonda District, Toba Regency. Conclusion: For Health Workers This research is expected to be used as a reference, especially by midwives who have worked in the field to pay attention to various factors that can affect the length of the second stage of labor, as a guide for midwives to provide health education to pregnant women about the effects of exercise.